Information processing underlying gaze control (Pergamon studies in neuroscience, 1994)
Information Processing Underlying Gaze Control covers the proceedings of the Satellite Workshop to the 16th European Neuroscience Association. The book presents materials concerning the computational properties of neuronal circuits underlying gaze control. The book contains 44 papers, which are organized into seven sections. The first section deals with the morphology and physiology of extraocular motor nuclei. Section II tackles the anatomo-functional organization of the saccadic system, and Section III covers the vestibular and otolithic systems. Section IV discusses the optokinetic and smoo